Read leadership books. Become a leader. - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
When Apple co-founder Steve Jobs died in October, there was a tremendous outpouring of grief from millions of people around the world. It was all the more remarkable that they were celebrating and paying tribute to the life of someone who was neither a humanitarian nor a revered statesman.